Design of Single-Tuned Passive Harmonic Filter to Meet Ieee-519 Standard By Means of Quality-Factor Manipulations - Wong Jee Keen Raymond, Yiauw Kah Haur, Teo Jay Son, Lum Kin Yun (International Journal of Advanced Science and Technology, 2020)
Electrical system is designed to work in an ideal sinusoidal voltage and the current waveform is at the same frequency. Nevertheless, harmonics pollution will occur whenever there are nonlinear loads connected to the system. The approach to solve this problem is by implementing a harmonic filter to reduce the 5th and 7th harmonics content. These harmonics are the primary concern due to the magnitude of a harmonic will reduce as its order increase. It causes the impact brought by the lower order harmonics will be relatively more substantial. A single-tuned passive filter is known as the simplest, cost-effective, and widely found in the industry compared to other filters. To optimise the design of the filter, by manipulating the